Dendritic cell phenotype and function in a 3D co-culture model of patient-derived metastatic colorectal cancer organoids - Subtil, Beatriz; Iyer, Kirti K.; Poel, Dennis; Bakkerus, Lotte; Gorris, Mark A. J.; Escalona, Jorge Cuenca; Dries, Koen van den; Cambi, Alessandra; Verheul, Henk M. W.; de Vries, I. Jolanda M.; Tauriello, Daniele V. F. (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) remains one of the most aggressive and lethal cancers, with metastasis accounting for most deaths. As such, there is an unmet need for improved therapies for metastatic CRC (mCRC). Currently, the research focus is shifting towards the reciprocal interactions within the tumor microenvironment (TME), which prevent tumor clearance by the immune system. Dendritic cells (DCs) play a key role in the initiation and amplification of anti-tumor immune responses and in driving the clinical success of immunotherapies. Dissecting the interactions between DCs and CRC cells may open doors to identifying key mediators in tumor progression, and possible therapeutic targets. This requires representative, robust and versatile models and tools. Currently, there is a shortage of such in vitro systems to model the CRC TME and its tumor-immune cell interactions. Here we develop and establish a dynamic organotypic 3D co-culture system to recapitulate and untangle the interactions between DCs and patient-derived mCRC tumor organoids. To our knowledge, this is the first study to investigate human DCs in a tumor organoid context. This system reveals how mCRC organoids modulate and shape monocyte-derived DCs (MoDCs) behavior, phenotype, and function, within a collagen matrix, using techniques such as brightfield and fluorescence microscopy, flow cytometry, and fluorescence-activated cell sorting. Our 3D co-culture model shows high viability and extensive interaction between DCs and tumor organoids, and its structure resembles patient tissue sections. Furthermore, it is possible to retrieve DCs from the co-cultures and characterize their phenotypic and functional profile. In our study, the expression of activation markers in both mature and immature DCs and their ability to activate T cells were impacted by co-culture with tumor organoids. In the future, this direct co-culture platform can be adapted and exploited to study the CRC-DC interplay in more detail, enabling novel and broader insights into CRC-driven DC (dys)function.